Trends and inequalities in the nutritional status of adolescent girls and adult women in sub-Saharan Africa since 2000: A cross-sectional series study - Jiwani, Safia S.; Gatica-Domínguez, Giovanna; Crochemore-Silva, Inacio; Maïga, Abdoulaye; Walton, Shelley; Verstraeten, Roosmarijn (BMJ, 2020)
Evidence on the rate at which the double burden of malnutrition unfolds is limited. We quantified trends and inequalities in the nutritional status of adolescent girls and adult women in sub-Saharan Africa.